Bilingualism as resource or obstacle? Educational tensions in contrasting Norwegian school settings - Smeplass, Eli (Frontiers in Education, 2026)
Increasing linguistic diversity in schools has intensified debates about how bilingualism is understood and handled within educational institutions. The analysis draws on empirical material from the Nordic Unequal Childhood project (2019–2024) and focuses on two contrasting Grade 5 classrooms in the same Norwegian city, situated in schools with markedly different socioeconomic and linguistic profiles. Using a qualitative, theoretically informed approach, the article is based on analytic vignettes reconstructed from the author's fieldnotes written during data collection activities in classrooms and school visits. Integrating research on bilingualism with neo-institutional theory and perspectives on inclusion, recognition, and resilience, the article introduces the concept of welfare capital to capture how access to institutional recognition shapes children's possibilities for participation. The findings show that bilingual practices embedded in different classroom ecologies are evaluated through distinct institutional lenses, shaped by local norms, teacher expectations, and the symbolic status attached to particular languages and forms of participation. These institutional readings—rather than linguistic competence alone—condition whether bilingualism becomes legible as a contribution to learning and inclusion or as a problem to be corrected. The article concludes by discussing implications for multilingual pedagogy and institutional practice in welfare-state schooling.